PS9:177 Lupus nephritis – clinicopathological correlation and renal outcome. (21st March 2018) - Rajasekharan Nair, R; Harish, P; Seethalekshmy, S; Kurian, G; Mathew, A; Paul, Z; Sreedharan, S
Abstract : Renal manifestation is one of the most severe complications of SLE and the clinical presentation of lupus nephritis (LN) is variable, ranging from mild asymptomatic proteinuria, renal failure to rapidly progressive glomerulonephritis. Performing renal biopsies is needed to determine the prognosis and to guide treatment in LN. Purpose and methods: To correlate the clinical, biochemical and histopathological findings in patients with biopsy proven LN and to study the renal outcome. Retrospective analysis of 100 cases of kidney biopsy proven Lupus Nephritis was done, analysed by WHO and ISN RPS Classification of Lupus Nephritis 2003. Results: 82 were female and 18 males. Extra renal manifestations in 72 cases while rest 28 had purely renal involvement. Biopsy finding showed the following class : 8 cases of class II, 29 cases of class III, 32 cases of class IV and 3 cases of class V. The remaining 28 showed combined class with predominant being class III+IV. Significant microscopic hematuria, impaired GFR, proteinuria, anaemia, hypoalbuminemia, hypertension, and positive anti- dsDNA, low C3 were associated with the worst class, that is, class IV. Most of the patients with class IV or V had nephrotic range proteinuria and low serum albumin levels. These parameters were also correlated with high renal pathological activity and chronicity index. 24 had renal failure at the time of biopsy (mean S.creatinine 2.12 mg/dl) followed up period of 3 years. With treatment, for 12 patients renal functions improved with creatinine improving to mean value of 1.26 mg/dl. 4 patients went into severe renal failure requiring hemodialysis while 6 patients were lost to follow up. 76 patients had normal renal functions at the time of presentation with an average S.creatinine of 0.86 mg/dl. 3 patients went into ESRD. 15 patients lost follow up. Conclusions: Clinical, laboratory findings and renal biopsy are clinically valuable in identifying different renal classifications of lupus pathology, and to plan therapeutic strategies accordingly. LN class IV G was the most common and had a reduced renal survival with significant high activity and chronicity scores.